Sustainability of buffalo farming in different environments in the world - Antonio Borghese; Vittoria Lucia Barile; Antonella Chiariotti (Revista Científica)
The domestic buffalo (Bubalus bubalis) plays a strategic role in the world for the economy and society. 203.9 million heads on the planet represent this species and produce 137 million tons of milk and 4.3 million tons of meat (+18.7% and +8.2% increase from 2015 to 2021, respectively). Buffalo products are essential for the human requirements of proteins of high nutritional value. These requirements will increase rapidly in the future with the growth of the human population. Therefore, the buffalo has and will have more of a strategic role in Governments’ economic programs in many countries. The buffalo is a long-living ruminant with a high capacity to convert fiber into energy and adapt in complex areas such as marshlands, Iraq, or Bangladesh, or in hot and humid climates where other ruminants cannot survive. Buffalo is a social and family animal in small villages in Southeast Asia, where it is used mainly in the rice fields as a draught animal producing milk essential for the children’s nutrition, meat, leather, manure, horns, and bones. Thanks to its great adaptability, buffalo can be bred both in intensive and extensive systems, as in South American countries where natural pastures are highly available. In this paper, the contributions of local breeds and cosmopolitan dairy breeds to sustain protein production, maintain the land’s biodiversity, and sustain the livelihood of populations are reported according to the different farming systems.